Questions kids ask about words and expressions - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Questions Kids Ask About Words and Expressions answers children's curious questions about language, explaining the meanings, origins, and uses of words and expressions in a fun and informative way.